(untitled) (Asian Journal of Current Engineering and Maths, 2013)
In this paper we discuss new type of continuous functions called slightly Î²gâˆ’continuous; somewhat Î²g-continuous and somewhat Î²g-open functions; its properties and interrelation with other such functions are studied.